Synthesis, characterization, structural elucidation, electrochemistry, DNA binding study, micellization behaviour and antioxidant activity of the Cu(II) carboxylate complexes. (1st March 2020) - Iqbal, Muhammad; Karim, Amir; Ali, Saqib; Nawaz Tahir, Muhammad; Sohail, Manzar
Graphical abstract: Highlights: Synthesis of bi-nuclear copper(II) complexes. Characterization through FT-IR, UV–Visible, ESR, electrochemical and powder and single crystal XRD techniques. Structural description. DNA-binding and miclellization behavior. Exhibition of improved properties. Abstract: New dimeric paddlewheel copper(II) mixed ligand complexes were synthesized having general formulae [(py)Cu(L)4 Cu(py)] (1), [(clpy)Cu(L*)4 Cu(clpy)] (2) and [(py)Cu(L°)4 Cu(py)] (3) where HL = 4-bromophenylacetic acid, HL* = phenyl acetic acid, HL° = 2-nitrophenylacetic acid, py = pyridine, clpy = 2-chloropyridine and characterized via FT-IR, powder and single crystal XRD, electrochemical solution studies and electron spin resonance spectroscopy. The resultant structures are dimeric paddlewheel where the carboxylate ligands act as bridges between two copper ions and pyridine acts as apical ligand leading to a square pyramidal geometry around each copper. The purity and crystalline nature of the complexes was checked by powder XRD technique. ESR spectra of the copper(II) complexes gave a sharp peak with g values = 1.443 (1) 1.512 (2) and 1.391 (3). The electrochemical studies showed diffusion controlled processes with diffusion co-efficient Do values = 3.68 × 10 −6 cm 2 s −1 (1) and 3.63 × 10 −6 cm 2 s −1 (3). Moreover, the complex-DNA interaction was studied by viscosity measurement, spectrofluorometry, cyclic voltammetry and UV–Visible spectrophotometry, the latter two yielding binding constant, Kb values = 4.0497 × 10 4  M −1 and 1.703 × 10 4  M −1 (1) and 4.117 × 10 4  M −1 and 1.743 × 10 4  M −1 (3), respectively. The complexes 1 and 2 showed moderate scavenging activity for the radical 2, 2-diphenyl-1-picryl-hydrazil. Micellization behaviour was studied with cationic surfactant CTAB using conductivity meter and UV–Visible spectrophotometer showing that all the complexes have increased solubility with the addition of surfactant. These initial studies heralded good biological potential of the complexes.